Quantifying the Socio-Economic Benefits of Transport: Roundtable summaries and conclusions - Daniel Veryard (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
Socio-economic cost-benefit analysis (CBA) is a powerful framework that can be very useful to governments making investment decisions. However the standard application of transport CBA has room for improvement. This paper describes efforts to improve the quality of transport CBA and its applicability to decision making. Three areas are addressed in detail: strategies for making the most of CBA, valuing and forecasting reliability benefits, and capturing wider economic impacts. The report is based on the papers and discussions at a roundtable meeting of 30 experts held in Paris in November 2015. Roundtable participants took the view that a multi-faceted approach is needed to address the shortfalls; CBA theory and practice need to be gradually expanded to incorporate more impacts in the rigorous valuation and forecasting framework; and CBA results need to be more effectively linked to other criteria in the broader decision-making framework, including by bringing in a more diverse evidence base.
Keywords: 330; Infrastrukturpolitik; Verkehrsinfrastruktur; Kosten-Nutzen-Analyse